THE DETERMINANT OF FINANCIAL INFORMATION DISCLOSURE ON INDONESIAN LGs WEBSITE - Kurniawan Cahyo Utomo; Y Anni Aryani (Asia Pacific Fraud Journal, 2016)
This research aims to find out the effect of size, leverage, wealth, audit opinion, liquidity, and press visibility of Local Governments (LGs) on the financial information disclosure through Indonesian LGs website. Center for Regional Information Study (Pattiro) states that only 28% of LGs disclose their financial information through website, and this proves lack of public transparency. This research method is using multiple linear regression. The population is 456 Local Governments (LGs) in Indonesia, with the research sample as many as 187 LGs conducted using purposive sampling method. The type of research data is secondary data. Empirical results show that size and wealth have positive effect on the financial information disclosure through website. Press visibility has negative effect on the financial information disclosure through website. While leverage, audit opinion, and liquidity do not have effect on the financial information disclosure through website. The implication of this research is that The Ministry of Home Affairs could develop a system of reward and punishment to motivate the LGs to improve their level of financial information disclosure through the website.